2015
DOI: 10.5604/12314005.1138269
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Repairs Performed Within the Emergency Repair Subsystem of Municipal Bus Transportation

Abstract: In this paper there have been presented results of an analysis of repair efficiency for an emergency repair subsystem (technical service units) in a selected transportation system. The research object was a real system of municipal transportation, in a given urban agglomeration. Experimental data, necessary to determine values of indexes describing efficiency of repairs performed by the technical service units, come from a selected group of technical objects (city buses) used in the analyzed system. The data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This applies to issues related to the selection of the optimal maintenance and repair strategy, as well as the assessment of the operation of subsystems for ensuring the suitability of service and repair stations. The papers [4,5] propose methods of shaping the readiness of technical back-up stations, while the publications [6,7] present methods for evaluating the effectiveness and efficiency of processes carried out at maintenance and repair stations. Paper [8] presents a method for determining the structure that can be coupled stations in vehicle service systems, while the method of determining the technically justified number of service and repair stations in transport systems is described in paper [9].…”
Section: Introductionmentioning
confidence: 99%
“…This applies to issues related to the selection of the optimal maintenance and repair strategy, as well as the assessment of the operation of subsystems for ensuring the suitability of service and repair stations. The papers [4,5] propose methods of shaping the readiness of technical back-up stations, while the publications [6,7] present methods for evaluating the effectiveness and efficiency of processes carried out at maintenance and repair stations. Paper [8] presents a method for determining the structure that can be coupled stations in vehicle service systems, while the method of determining the technically justified number of service and repair stations in transport systems is described in paper [9].…”
Section: Introductionmentioning
confidence: 99%
“…It reflects issues connected to selection of optimal strategy (policy) of servicing and repair as well as evaluation of the operation of serviceability assurance subsystems (service and repair posts). The authors of papers [6,11] suggested that the methods of shaping the availability of technical backup area posts, whereas papers [9,10] discuss the methods of the evaluation of the effectiveness and productivity of processes carried out at service and repair posts. Paper [3] discusses methods of defining the structure which may link posts at vehicle service systems, whereas the way of defining technically valid number of service and repair posts in transport systems was described in paper [8].…”
Section: Introductionmentioning
confidence: 99%
“…Papers [3,4,5,10] discuss issues connected with modeling and organization of technical objects service systems. The authors of papers [6,15] suggested that the methods of shaping the availability of technical backup area posts, whereas papers [7,13,14] discuss the methods of the evaluation of the effectiveness and productivity of processes carried out at service and repair posts. Paper [1] discusses methods of defining the structure which may link posts at vehicle service systems, whereas the way of defining technically valid number of service and repair posts in transport systems was described in paper [8].…”
Section: Introductionmentioning
confidence: 99%